Influence of Stimulus Intensity on Multimodal Integration in the Startle Escape System of Goldfish - McIntyre, Camille; Preuss, Thomas (Frontiers in Neural Circuits, 2019)
Processing of multimodal information is essential for an organism to respond to environmental events. However, how multimodal integration in neurons translates into behavior is far from clear. Here we studied the integration of biological relevant visual and audio information in the goldfish startle escape behavior triggered by the paired Mauther cell i.e., in neurons that provide the biological interface between sensory integration and behavior. Results show adding a sound pip early during a visual loom (i.e., at a time of reduced visual effectiveness) caused a supralinear increase in startle responsiveness when compared to the linear addition of the individual effectiveness of the two stimuli. However, adding a sound pip late during the loom (high visual effectiveness) increased responsiveness consistent with linear multimodal integration. This suggests common multimodal integration processes such as inverse effectiveness is computed in individual neurons that directly initiate vital behavioral decisions.